The globalization of supermax prisons - Ross, Jeffrey Ian; Wacquant, Loïc (Critical issues in crime and society, 2013)
""Supermax" prisons, conceived by the United States in the early 1980s, are typically reserved for convicted political criminals such as terrorists and spies and for other inmates who are considered to pose a serious ongoing threat to the wider community, to the security of correctional institutions, or to the safety of other inmates. Prisoners are usually restricted to their cells for up to twenty-three hours a day and typically have minimal contact with other inmates and correctional staff. Not only does the Federal Bureau of Prisons operate one of these facilities, but almost every state has either a supermax wing or stand-alone supermax prison. The Globalization of Supermax Prisons examines why nine advanced industrialized countries have adopted the supermax prototype, paying particular attention to the economic, social, and political processes that have affected each state. Featuring essays that look at the U.S.-run prisons of Abu Ghraib and Guantánamo, this collection seeks to determine if the American model is the basis for the establishment of these facilities and considers such issues as the support or opposition to the building of a supermax and why opposition efforts failed; the allegation of human rights abuses within these prisons; and the extent to which the decision to build a supermax was influenced by developments in the United States. Additionally, contributors address such domestic matters as the role of crime rates, media sensationalism, and terrorism in each country's decision to build a supermax prison"--Publisher's website